Prefrontal tDCS Decreases Pain in Patients with Multiple Sclerosis - Ayache, Samar S.; Palm, Ulrich; Chalah, Moussa A.; Al-Ani, Tarik; Brignol, Arnaud; Abdellaoui, Mohamed; Dimitri, Dalia; Sorel, Marc; Créange, Alain; Lefaucheur, Jean-Pascal (Frontiers in Neuroscience, 2016)
Background In the last few years, transcranial direct current stimulation (tDCS) has emerged as an appealing therapeutic option to improve brain functions. Promising data support the role of prefrontal tDCS in augmenting cognitive performance and ameliorating several neuropsychiatric symptoms, namely pain, fatigue, mood disturbances, and attentional impairment. Such symptoms are commonly encountered in patients with multiple sclerosis (MS). Objective The main objective of the current work was to evaluate the tDCS effects over the left dorsolateral prefrontal cortex (DLPFC) on pain in MS patients. Our secondary outcomes were to study its influence on attention, fatigue and mood. Materials and Method 16 MS patients with chronic neuropathic pain were enrolled in a randomized, sham-controlled, and cross-over study. Patients randomly received two anodal tDCS blocks (active or sham), each consisting of three consecutive daily tDCS sessions, and held apart by three weeks. Evaluations took place before and after each block. To evaluate pain, we used the Brief Pain Inventory (BPI) and the Visual Analogue Scale (VAS). Attention was assessed using neurophysiological parameters and the Attention Network Test (ANT). Changes in mood and fatigue were measured using various scales. Results Compared to sham, active tDCS yielded significant analgesic effects according to VAS and BPI global scales. There were no effects of any block on mood, fatigue or attention. Conclusion Based on our results, anodal tDCS over the left DLPFC appears to act in a selective manner and would ameliorate specific symptoms, particularly neuropathic pain. Analgesia might have occurred through the modulation of the emotional pain network. Attention, mood and fatigue were not improved in this work. This could be partly attributed to the short protocol duration, the small sample size and the heterogeneity of our MS cohort. Future large-scale studies can benefit from comparing the tDCS effects over different cortical sites, changing the stimulation montage, prolonging the duration of protocol, and coupling tDCS with neuroimaging techniques for a better understanding of its possible mechanism of action.